Regulatory Gaps in Protecting Children’s Constitutional Rights against Digital Microtransactions in Indonesia’s Online Gaming Ecosystem - Isharyanto Isharyanto; Achmad Fawaid; Ismail Marzuki (Khazanah Hukum, 2026)
This article examines regulatory gaps in protecting children’s constitutional rights against digital microtransactions in Indonesia’s online gaming ecosystem. The study aims to analyze how monetization mechanisms such as loot boxes, gacha systems, pay-to-win designs, and other persuasive interfaces may expose children to risks of digital economic exploitation; to evaluate the adequacy of Indonesia’s legal framework in addressing those risks; and to formulate a child-centered regulatory model for online gaming governance. This research employs normative legal methods through doctrinal, comparative, and conceptual approaches. The doctrinal approach is used to examine Indonesian positive law, the comparative approach analyzes regulatory responses in the United Kingdom, the Netherlands, South Korea, and Japan, and the conceptual approach interprets constitutional protection and the principle of the best interests of the child. The findings show that digital microtransactions function as integrated monetization architectures that may exploit children’s cognitive, behavioral, and social vulnerabilities. Although Indonesia already possesses relevant legal instruments, including Article 28B paragraph (2) of the 1945 Constitution, the Child Protection Law, the Consumer Protection Law, the ITE Law, and Government Regulation No. 17 of 2025, the current framework remains fragmented, general, and insufficiently responsive to microtransaction-specific risks. The study implies the need for a child-centered regulatory framework based on design protection, transparency obligations, platform accountability, and coordinated institutional supervision. The originality of this article lies in repositioning digital microtransactions from a predominantly psychological and market-based issue into a constitutional child-rights issue within Indonesia’s digital legal order.